An observational study to determine the efficacy of FOGSI gestosis score as a predictor of pre-eclampsia and Ecosprin prophylaxis as a preventive intervention - Sharma, Sonali; Kaur, Ibadatpreet; Grover, Suparna; Kaur, Amritpal (International Journal of Research in Medical Sciences, 2025)
Background: FOGSI gestosis score is a simple risk model devised for preeclampsia screening and prediction. Each risk factor is given score of 1, 2 or 3 based on severity. A total score of ≥3, implies ‘at risk’ for developing preeclampsia warranting closer monitoring and management. Also, Ecosprin prophylaxis in these high-risk pregnancies can reduce the incidence of early onset preeclampsia as well as maternal and neonatal morbidity and mortality. Methods: This prospective OBSERVATIONAL study was conducted at GMC Amritsar, involving 100 pregnant women at ≤24 weeks of gestation (Group A), screened using gestosis score. Participants identified as high-risk (score ≥3) received prophylactic Ecosprin and monitored until 6 weeks postpartum for maternal and neonatal outcomes which were compared with 145 unbooked, already known cases of preeclampsia/eclampsia (group B). Results: Among 100 participants screened as per gestosis score, 29% were high risk and 71% low risk. Preeclampsia developed in 31% of high-risk versus 4.2% of low-risk participants (IRR=8.98, p=0.0002). Significant predictors included anaemia, primigravida status, BMI>30 and MAP>85 mmHg. Preterm birth, FGR, unfavourable APGAR score and perinatal mortality were more common in the high-risk group. The score demonstrated 82.35% sensitivity, 82.69% specificity, 43.75% PPV, 96.63% NPV, and 82.64% accuracy in predicting Preeclampsia, indicating good screening potential. Conclusions: Gestosis score is low cost, noninvasive screening tool for predicting preeclampsia and adverse pregnancy outcomes, particularly in resource-constrained settings. Early Ecosprin prophylaxis significantly reduces the incidence and severity of complications in high-risk pregnancies.